Piloto semi-automático para auxiliar na captura de vídeos usando veículos aéreos não tripulados - Rüdiger, Gustavo Teixeira (2017)
This work presents a solution to facilitate the use of UAVs (Unmaned Aerial Vehicles) by aerial filmmaking enthusiasts. Beginners pilots with little experience have dificulties performing complex movements. This project aim to allow these pilots to perform these movements more easily with the help of an semi-autonomous pilot implemented on the UAV controller. To acomplish this, an open source autopilot software is used as base to develop new flight modes. This new flight modes execute movements that were created inspired by the tecnologies and camera moves used in cinema. After tests were made in a simulated enviroment, an quadricopter was assembled to make tests in a real enviroment. As result, the flight modes developed helped to execute the movements in less time and with better quality.